2020
DOI: 10.1002/mrm.28388
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort echo time quantitative susceptibility mapping (UTE‐QSM) for detection of hemosiderin deposition in hemophilic arthropathy: A feasibility study

Abstract: Purpose The purpose of this study was to investigate the feasibility of ultrashort echo time quantitative susceptibility mapping (UTE‐QSM) for assessment of hemosiderin deposition in the joints of hemophilic patients. Methods The UTE‐QSM technique was based on three sets of dual‐echo 3D UTE Cones data acquired with TEs of 0.032/2.8, 0.2/3.6, and 0.4/4.4 ms. The images were processed with iterative decomposition of water and fat with echo asymmetry and least‐squares estimation to estimate the B0 field map in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…The UTE Cones (UTE‐Cones) sequence uses twisted trajectories (ie, 3D spiral arms) to efficiently encode the 3D k‐space for data readout 22,23 . Moreover, various data analysis and signal preparation schemes including T 1 and T2 mapping, 24‐26 quantitative susceptibility mapping, 27‐30 magnetization transfer, 31,32 adiabatic inversion recovery, 33‐36 and adiabatic T 1ρ spin locking 37‐39 have been combined with Cones sampling for quantitative UTE imaging, further demonstrating the efficacy and adaptability of the UTE‐Cones sequence in morphological and quantitative imaging of short T 2 tissues such as the osteochondral junction (OCJ), menisci, ligaments, tendons, cortical bone, and hemosiderin.…”
Section: Introductionmentioning
confidence: 99%
“…The UTE Cones (UTE‐Cones) sequence uses twisted trajectories (ie, 3D spiral arms) to efficiently encode the 3D k‐space for data readout 22,23 . Moreover, various data analysis and signal preparation schemes including T 1 and T2 mapping, 24‐26 quantitative susceptibility mapping, 27‐30 magnetization transfer, 31,32 adiabatic inversion recovery, 33‐36 and adiabatic T 1ρ spin locking 37‐39 have been combined with Cones sampling for quantitative UTE imaging, further demonstrating the efficacy and adaptability of the UTE‐Cones sequence in morphological and quantitative imaging of short T 2 tissues such as the osteochondral junction (OCJ), menisci, ligaments, tendons, cortical bone, and hemosiderin.…”
Section: Introductionmentioning
confidence: 99%
“…22 Previous studies have shown that an extension of the wellknown IDEAL algorithm can be used to generate water, fat, and quantitative susceptibility maps. 23,24 Beyond that, the water-and fat-separated images were used to suppress long T 2 components which proves itself beneficial in pseudo-CT imaging or in the context of PET attenuation map generation. [22][23][24][25][26][27][28] However, also typical UTE-Dixon imaging requires the acquisition of multiple echoes which prolong the repetition time (TR) and conventional Dixon does not consider the short T * 2 decay of water signal.…”
Section: Introductionmentioning
confidence: 99%
“…The potential clinical application of UTE-QSM has been shown in several papers. For example, UTE-QSM was used for detecting hemosiderin deposition in patients with hemophilic arthropathy ( 22 ). The susceptibility was presented as high intensity in affected regions with high iron concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, related studies mainly focused on imaging the cortical bone and didn’t quantify soft tissue susceptibility. UTE-QSM has not been applied to explore the articular cartilage of human in vivo ( 21 , 22 ). Simultaneous susceptibility mapping of the articular cartilage and cortical bone with a single MRI scan is still lacking and highly needed.…”
Section: Introductionmentioning
confidence: 99%